2020
DOI: 10.1136/bmjopen-2019-036355
|View full text |Cite
|
Sign up to set email alerts
|

On the path towards universal coverage of hepatitis C treatment among people receiving opioid agonist therapy (OAT) in Norway: a prospective cohort study from 2013 to 2017

Abstract: ObjectivesWe aimed to calculate cumulative hepatitis C virus (HCV) treatment coverage among individuals enrolled in opioid agonist therapy (OAT) in Norway between 2013 and 2017 and to document the treatment transition to direct-acting antiviral (DAA) agents. Moreover, we aimed to describe adherence to DAAs in the same cohort.DesignProspective cohort, registry data.SettingSpecialist healthcare service (secondary)Participants and outcomesThis observational study was based on data from The Norwegian Prescription … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…A newly published report from the Norwegian Institute of Public Health indicated that Norway has come a long way in eradicating hepatitis C in the general population, and that the prevalence among people who inject drugs (PWID) decreased substantially since 2016 [ 42 ]. More patients currently receive hepatitis C treatment than in previous years [ 24 , 43 , 44 ]. Based on the latest Norwegian OMT status report, > 35% of patients in Norwegian OMT have completed treatment for hepatitis C, in addition to nearly 40% not having active disease based on antigen testing.…”
Section: Discussionmentioning
confidence: 99%
“…A newly published report from the Norwegian Institute of Public Health indicated that Norway has come a long way in eradicating hepatitis C in the general population, and that the prevalence among people who inject drugs (PWID) decreased substantially since 2016 [ 42 ]. More patients currently receive hepatitis C treatment than in previous years [ 24 , 43 , 44 ]. Based on the latest Norwegian OMT status report, > 35% of patients in Norwegian OMT have completed treatment for hepatitis C, in addition to nearly 40% not having active disease based on antigen testing.…”
Section: Discussionmentioning
confidence: 99%
“…Despite safe and effective hepatitis C virus treatments in Norway [33], barriers often prevent those most in need from accessing them [3], necessitating further efforts. To improve outcomes when cancer has developed, health services should focus upon improving access to cancer treatment for people with opioid use-related disorders and address potential barriers to care [34].…”
Section: Discussionmentioning
confidence: 99%
“…An important approach to reducing cancer‐related mortality is to provide preventive measures as early in life as possible, such as smoking cessation, reduced injecting drug behaviour and alcohol intake, healthy diet and sufficient physical activity [32]. Despite safe and effective hepatitis C virus treatments in Norway [33], barriers often prevent those most in need from accessing them [3], necessitating further efforts. To improve outcomes when cancer has developed, health services should focus upon improving access to cancer treatment for people with opioid use‐related disorders and address potential barriers to care [34].…”
Section: Discussionmentioning
confidence: 99%
“…Transmission of HCV is high among people who inject drugs (PWID), people with a history of injection drug use or a history of recent substance use receiving opioid maintenance treatment (OMT) [6,7]. Among patients receiving OMT in Norway, about half had chronic HCV infection [8]. Liver disease and substance-related overdose are equally signifcant causes of death among people with opioid dependence under the age of 50 [9,10].…”
Section: Introductionmentioning
confidence: 99%